Education and HIV/AIDS : a window of hope - World Bank. (Washington, DC : World Bank, 2002)
The central message of this paper is that the education of children and youth merits the highest priority in a world afflicted by HIV/AIDS. This is because a good basic education ranks among the most effective and cost effective means of preventing HIV. This is a very significant and comprehensive bool from the world bank, where there is such well developed capacity to get a holistic view of what education needs to do in the overall struggle with HIV/AIDS.
Includes bibliographical references (p. 71-78).
nmn, 08/08/2016
Loans
Keywords: AIDS (Disease); Education; Government aid to education